Ocular thelaziasis: A case report from Assam, India - Chowdhury, Runumi (Trop Parasitol, 2018)
We report here a case of human ocular thelaziasis that was discovered accidentally during cataract surgery. A 58-year-old farmer attended an eye camp for diminished vision of the left eye, which was diagnosed later on as cataract. He was referred to a tertiary care hospital in Assam. During the cataract surgery, two small, motile, chalky white, translucent worms were removed from the left fornix. They were identified as female Thelazia callipaeda. Rare occurrence of this disease and its association with both extra and intraocular manifestations leading to ocular morbidity is the rationale for presenting this case.